Kepastian Hukum Anak Perkawinan Campuran Akibat Pemalsuan Dokumen Perkawinan - Rizka Putri Awwaliyah; Sony Juniarti; Muhammad Haekal; Trisnawati Trisnawati; Hafidz Rabbani Kurniawan (Universitas Sains dan Teknologi Komputer, 2023)
Marriage is a legal act involving two people in establishing a social bond as a husband and wife in a household which gives rise to legal consequences in the form of rights and obligations for the subjects therein to submit and obey in accordance with the provisions of Law no. 1 of 1974 as amended by Law no. 16 of 2019 concerning Marriage. Actions that deviate from the provisions of the Marriage Law can result in the annulment of the marriage so that the marriage is considered null and void. The marriage annulment case that has attracted public attention is between Jessica Iskandar and Ludwig, a German citizen, as a case of mixed marriage annulment involving Indonesian citizens and foreigners. The problems that arise in this case are indications of falsification of marriage documents and the legal consequences for the children resulting from the marriage. This research aims to find out about the legal consequences for children who emerge from mixed marriages involving fake documents and the legal protection for these children. The research method used is qualitative with an empirical normative approach with data collection using literature study and descriptive analysis. The research results show that children resulting from mixed marriages have the right to choose citizenship at the age of 18 and are entitled to dual citizenship rights, property rights, inheritance rights and legal protection.